Evaluation of the degradation of mortar with volcanic tuff replacement via destructive and non-destructive testing - Hebah Mohammad Al-jabali; Walid. Fouad Edris; Mahmoud Al-Tamimi; Abd Al-Kader A. Al Sayed; Tarek Ibrahim Selouma (Case Studies in Construction Materials)
This study examines the impact of volcanic tuff replacements (0 %, 20 %, and 30 %) on the durability and mechanical properties of mortar subjected to sulfate degradation over time. The samples were submerged in a 10 % sulfate solution and subjected to wet and dry cycles as part of an accelerated deterioration process. Mortar samples underwent degradation for 1, 30, 60, 90, and 120 days. Tests for compressive strength, porosity, expansion, SEM analysis, and ultrasonic pulse velocity (UPV) were conducted. The initial compressive strength prior to the degradation process demonstrated a decreasing trend as the level of volcanic tuff replacement increased. On the other hand, sulfate-degraded samples showed an initial increase in compressive strength up to 90 days, followed by a decline till the end of exposure period. At 120 days of degradation, the compressive strength of the samples exhibited a noticeable decrease across all replacement levels when compared to the unexposed samples. The incorporation of volcanic tuff, particularly at higher replacement levels, demonstrated improved sulfate resistance compared to control samples, as reflected in reduced porosity, minimized expansion, and enhanced UPV values over time in both cube and prism samples. One hundred eighty standard cubes and Thirty-six prisms with dimensions of (50 × 50 × 50 mm3) and (25 × 25 × 285 mm3), respectively, were cast using three different mixes of the cement mortar. The study demonstrates a strong correlation between UPV and compressive strength, porosity, and expansion, indicating that higher tuff replacement enhances the durability of mortar under sulfate attack. These findings suggest that volcanic tuffs can significantly improve the longevity and performance of mortar in aggressive environments.